Real‐ and Q‐space travelling: multi‐dimensional distribution maps of crystal‐lattice strain (ϵ044) and tilt of suspended monolithic silicon nanowire structures. Issue 1 (18th December 2019) - Dolabella, Simone; Frison, Ruggero; Chahine, Gilbert A.; Richter, Carsten; Schulli, Tobias U.; Tasdemir, Zuhal; Alaca, B. Erdem; Leblebici, Yusuf; Dommann, Alex; Neels, Antonia
Abstract : A multiscale analytical approach is presented for understanding the structure of micro‐ and nano‐fabricated nanowire‐based sensors. Using scanning X‐ray diffraction microscopy, crystal deformation is evaluated with respect to lattice strain and tilt caused by the manufacturing process of a silicon monolith. Abstract : Silicon nanowire‐based sensors find many applications in micro‐ and nano‐electromechanical systems, thanks to their unique characteristics of flexibility and strength that emerge at the nanoscale. This work is the first study of this class of micro‐ and nano‐fabricated silicon‐based structures adopting the scanning X‐ray diffraction microscopy technique for mapping the in‐plane crystalline strain (ϵ044 ) and tilt of a device which includes pillars with suspended nanowires on a substrate. It is shown how the micro‐ and nanostructures of this new type of nanowire system are influenced by critical steps of the fabrication process, such as electron‐beam lithography and deep reactive ion etching. X‐ray analysis performed on the 044 reflection shows a very low level of lattice strain (<0.00025 Δ d / d ) but a significant degree of lattice tilt (up to 0.214°). This work imparts new insights into the crystal structure of micro‐ and nanomaterial‐based sensors, and their relationship with critical steps of the fabrication process.